2016
DOI: 10.1038/cr.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival of porcine acute liver failure by a bioartificial liver device implanted with induced human functional hepatocytes

Abstract: Acute liver failure (ALF) is a life-threatening illness. The extracorporeal cell-based bioartificial liver (BAL) system could bridge liver transplantation and facilitate liver regeneration for ALF patients by providing metabolic detoxification and synthetic functions. Previous BAL systems, based on hepatoma cells and non-human hepatocytes, achieved limited clinical advances, largely due to poor hepatic functions, cumbersome preparation or safety concerns of these cells. We previously generated human functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 35 publications
(67 reference statements)
2
86
0
Order By: Relevance
“…Observation of ammonia depuration is an evidence of hepatic synthetic function and is an important feature to propose the device we present here for clinical application[21,22]. When this MBR was challenged with an ammonia overload it showed an effective detoxification of this detrimental metabolite, either when cold preserved or fresh LMOs were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Observation of ammonia depuration is an evidence of hepatic synthetic function and is an important feature to propose the device we present here for clinical application[21,22]. When this MBR was challenged with an ammonia overload it showed an effective detoxification of this detrimental metabolite, either when cold preserved or fresh LMOs were examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the latest study by Shi et al . () on pigs showed that 3 hours of BAL treatment on the first day after the ALF induction increased the survival rate of pigs up to 87.5% compared to 12.5% in the nontreated ALF group. This suggests that a short‐time exposure of a BAL to patient plasma might already be enough to support patients, while diminishing the risk of ALF or ACLF plasma toxic effects on BAL biocomponents.…”
Section: Effects Of Plasma Of Alf or Aclf Patients On Bal Functionmentioning
confidence: 99%
“…An artificial liver support system (ALSS) could be used as a bridge between liver failure and liver transplantation [5]. Before ALSS goes into clinical trials, establishment of an ideal experimental model in a large animal is desperately needed to test the feasibility, functionality, and safety [6, 7]. …”
Section: Introductionmentioning
confidence: 99%